Estudio de factibilidad para la producción de conservas de rambután ( achotillo ) en almíbar, en el cantón Quinsaloma, 2018. - Quinchiguano Ushiña, Carlos Mauricio (2019)
The objective of this project is to carry out a research for rambután production and commercialization in syrup, this work was carried out to take advantage abaut for fruit 40% overproduction of the rambután per hectare that exists in the enclosures around Quinsaloma Canton, this represents 8 tons of the 20 as total production, the most relevant method to highlight the project viability was a survey was conducted for the indirect beneficiaries of the canton. Likewise, to verify the hypothesis proposed, the Chi-square method was used, which was obtained as positive and reflected the research for the creation of a microenterprise. Among the most important results, it can be highlighted that this market to which de product is directed to social medium class, medium high and high, through the sample calculation of the population that resulted 382 households that were surveyed, through the application of linear forecasts the production for the year 2019 will generate a percentage of 85% of preserves units this considering that the equilibrium point is 124246 units of annual preservation. In the same way, the installed capacity of the production plant was analyzed, which will be 75% efficiency and productivity, as a result, a land of 677m2 will be used. Within the financial evaluation, relevant economic aspects were considered, that is to say, this project is feasible with 71%, so in the cost-benefit it is mentioned for every dollar invested it will generate 0.71 cents, of income that means that if the project is carried out not only would the microenterprise be created, but it would also boost entry to the national and international market, thus seeking a microenterprise to enter with a novel product in the market.